Shear and Bending Performance of Horizontal Laminated Bamboo Lumber Bonded with Urea-Formaldehyde and Preserved with Deltamethrin - Syaifudin, Tirana Novitri; Irawati, Inggar Septhia; Awaludin, Ali (Universiti Teknologi Malaysia, 2022)
Deltamethrin has potential to be used for bamboo strip preservation in laminated bamboo lumber (LBL) beam industry. However, there is a lack of information regarding the effect of deltamethrin preservation on the structural performance of the LBL beam. This study was intended to observe shear and bending performance of LBL beam made of Dendrocalamus asper, preserved by deltamethrin, and glued by urea-formaldehyde. The adhesive bonding strength test following ASTM D905 and MD Block method and static bending test based on ASTM D143 were performed toward preserved and unpreserved samples. The performance was observed by calculating adhesive bonding strength, MOE, MOR, ductility index, and investigating failure modes. The results show that the average adhesive bonding strength of the treated sample is 7.28 MPa (ASTM D905) and 7.03 MPa (MD Block), while the average adhesive bonding strength of the untreated sample is 7.67 MPa (ASTM D905) and 7.41 MPa (MD Block). The average MOE (modulus of elasticity) and MOR (modulus of rupture) of the treated specimen is 18,840 MPa and 110 MPa, respectively. The untreated specimen's average MOE and MOR are 18,199 MPa and 109 MPa, respectively. The average ductility index of untreated and treated specimens is 4.8 and 3.9, respectively. The adhesive bonding strength of treated and untreated samples are higher than the bamboo shear strength. The result indicates that deltamethrin has no significant effect on the adhesive bonding strength, MOR, and MOE of the LBL beam. The LBL beams show significant plastic deformation before final beam failure. © 2022 Penerbit UTM Press. All rights reserved.